Pengembangan Multimedia Pembelajaran Interaktif Berbasis Grafis Untuk Mata Pelajaran Pemrograman Dasar Menggunakan Model APPED Pada Jurusan Multimedia di SMK Negeri 4 Malang - Hanif Aulia Kusuma; Hanifah Muslimah Az-zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the impacts of the change in curriculum structure (from the 2006 curriculum to the 2013 curriculum) is that there are basic programming subjects in the Department of Multimedia class X which previously did not exist. This has caused problems, including the lack of relevant learning resources and the results of evaluating the function material while carrying out Lesson Study in the Multimedia-C class X, 28 students out of 37 students scored below the KKM (Minimum completeness criteria). These problems need to be developed in Interactive Learning Multimedia (MPI) using the APPED model to improve student learning outcomes. The results of the MPI product evaluation were declared valid by researchers at the ongoing evaluation stage, for the alpha test stage the assessment of material experts was 97.80% and included in the category of